HHO Gas Production Assessment for Different NaOH Concentrations and Electrode Plates Under Hydrostatic Pressure - Ummi Kultsum; Cahyo Jawoto Anggoro; Dewi Mahyunani; Andi Ibrahim Soumi (Engineering Proceedings)
Hydrogen generated through electrolysis is a feasible, sustainable energy source. HHO gas, a combination of hydrogen and oxygen generated via water electrolysis, is a clean and efficient energy source. The influence of NaOH electrolyte concentrations (2%, 4%, 6%, 8%, and 10%) and electrode plate numbers (2, 4, and 6) on HHO gas production and hydrostatic pressure will be examined in this study. Both NaOH concentration and electrode plate number increase HHO gas generation and hydrostatic pressure. A 10% NaOH concentration with six plates produced the most pressure and highest rate of hydrogen production.